Milton and the rabbis : Hebraism, Hellenism & Christianity - Shoulson, Jeffrey S. (Columbia University Press, 2001)
Taking as its starting point the long-standing characterization of Milton as a "Hebraic" writer, Milton and the Rabbis probes the limits of the relationship between the seventeenth-century English poet and polemicist and his Jewish antecedents. Shoulson's analysis moves back and forth between Milton's writings and Jewish writings of the first five centuries of the Common Era, collectively known as midrash. In exploring the historical and literary implications of these connections, Shoulson shows how Milton's text can inform a more nuanced reading of midrash just as midrash can offer new insights into Paradise Lost. Shoulson is unconvinced of a direct link between a specific collection of rabbinic writings and Milton's works